Development of Nanofiber Mats Impregnated With Ferula assa-foetida Essential Oil Nanogel for Antibacterial Wound Care - Mahmoud Osanloo; Sahar Fereydonpour; Abbas Abdollahi; Mojdeh Safari (International Journal of Biomaterials)
Bacterial infections pose significant threats to human health, and the rising issue of antibiotic resistance necessitates exploring alternative therapeutic strategies. In this study, Ferula assa-foetida essential oil (EO) as an herbal medicine was first analyzed using gas chromatography-mass spectrometry (GC-MS). Polycaprolactone-gelatin nanofibers were then prepared via electrospinning. Biological efficacies (antioxidant and antibacterial properties) of nanofibers impregnated with the nanogel containing the EO were finally investigated. As a result, the five major identified compounds were ethyl trifluoromethyl disulfide (33.6%), β-pinene (15.1%), δ-3-carene (6.6%), dihydro-β-agarofuran (6.0%), and γ-eudesmol (5.5%). Nanogel was developed from a primary nanoemulsion, with a 55 ± 7 nm droplet size and a zeta potential of −31 ± 2 mV. Nanofibers with a hydrophobic surface (contact angle (θ) 107°) impregnated with the nanogel demonstrated remarkable antibacterial efficacy, inhibiting the growth of Escherichia coli and Staphylococcus aureus by nearly 100% and Pseudomonas aeruginosa by 90%. These findings suggest that the developed formulation has the potential to serve as an effective antibacterial wound dressing, warranting further investigation.